Implementation of problem-based learning (PBL) model assisted by PAJURA media to improve learning outcomes of second-grade elementary school students - Ayu Lestari, Dyah; Sugiarti; Manggiasih , Nurina (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this research was to determine the improvement of students' learning outcomes by implementing the Problem-Based Learning (PBL) model assisted by PAJURA media in understanding the concepts of addition and subtraction operations on whole numbers. This study is classified as Classroom Action Research (CAR) comprising two cycles. The subjects are 27 second-grade students of SDN Mojorejo 1 Batu in the academic year 2022/2023. The data collection method in this research is through tests to gather students' learning outcomes data. The results of this study indicate that the implementation of the Problem-Based Learning (PBL) model assisted by PAJURA media can improve students' learning outcomes in understanding the concepts of addition and subtraction operations on whole numbers in grade 2. This improvement is evident in the student's learning outcomes. The initial data (pre-cycle) showed an average learning outcome of 67% with a mastery learning rate of 41%. After the implementation of the Problem-Based Learning (PBL) model assisted by PAJURA media in the first cycle, the average learning outcome increased to 79% with a mastery learning rate of 70%. Following the improvement in the second cycle, there was a further enhancement in the average learning outcome percentage, reaching 88%, with a mastery learning rate of 89%.